The crystal structure of tetrakis(6-phenylpyridine-2-carboxylato-κ2N,O)-bis(1H-pyrazol-3-ylamine-κ2 N:N)dicobalt(II) dihydrate, C27H23N5O5Co - Xiang Gao; Xi-Shi Tai (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C27H23N5O5Co, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 8.6503(7) Å, b = 11.1188(8) Å, c = 13.2711(11) Å, α = 79.185(7)°, β = 71.970(7)°, γ = 87.951(6)°, V = 1191.85(17) Å3, Z = 2, R gt(F) = 0.0450, wR ref(F 2) = 0.1143, T = 200 K.